Personal networks and locus of control in large urban centers of Argentina - Grande, Pablo De (Pontificia Universidad Católica del Perú, 2013)
This study analyzes the relationship between locus of control and interpersonal relations structures in Argentina. After a representative sample (n = 1500) of households in seven major urban centers (>200,000 inhabitants), it examines the relationship between the externality of locus of control and different aspects of personal networks of each respondent. The results show that people having more relations experiment lower levels of externality of locus of control. Likewise, lower levels of externality are informed when personal ties outside the neighborhood are available, as well as ties high educational level. In this regard, significant associations are verified between control and personal relations structures.